Modulation Instability of Terahertz Beams in Paraelectrics in a Wide Temperature Range - Grimalsky, V.; Koshevaya, S.; Esobedo-Alatorre, J.; Gomez-Badillo, Y.; Rapoport, Yu (2020 IEEE Ukrainian Microwave Week (UkrMW), 2020)
The nonlinear propagation of two-dimensional and three-dimensional terahertz electromagnetic beams in paralelectrics like SrTiO 3 is theoretically investigated in the temperature range T= 50 - 200 K. These beams are subject to the modulation instability that results in the formation of the sequence of short pulses from the long input envelope pulse. At smaller temperatures the nonlinearity behaves at smaller input amplitudes, whereas at higher temperatures the modulation instability can be observed at higher frequencies up till 1.5 THz. The initial focusing makes possible to reduce the input amplitudes for observing the modulation instability. Threedimensional beams are preferable for stable forming the sequences of picosecond envelope pulses.